Territorial Identities in Action - ILOVAN, Oana-Ramona (Presa Universitară Clujeană, 2021)
Collection Constructing Territorial Identities. Theory and Practice is coordinated by dr. Oana-Ramona Ilovan The collection appears under the aegis of the Territorial Identities and Development Research Centre, Faculty of Geography, Babeş-Bolyai University, Cluj-Napoca, Romania This collective volume contributes to the academic literature on the topic of territorial identity, providing professors, researchers and students with theoretical, methodological and applicative insights. Territorial identity is conceived as a social construct, undergoing constant changes, being influenced by a variety of physical and human factors (cf. Banini, Ilovan, 2021a, 2021b; Paasi, 2021).